Energy efficiency in virtual machines allocation for cloud data centers with lottery algorithm - Mehran Tarahomi; Mohammad Izadi (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Energy usage of data centers is a challenging and complex issue because computing applications and data are growing so quickly that increasingly larger servers and disks are needed to process them fast enough within the required time period. In the past few years, many approaches to virtual machine placement have been proposed. This study proposes a new approach for virtual machine allocation to physical hosts. Either minimizes the physical hosts and avoids the SLA violation. The proposed method in comparison to the other algorithms achieves better results.